Congenital Rubella: A Salient Cause of Congenital Heart Defects in Infants. (26th May 2021) - Gupta, Saniya; Verma, Sanjay; Dash, Nabaneeta; Goel, Malika; Rawat, Amit; Singh, Mini P; Rohit, Manoj Kumar; Kumar, Praveen
Abstract: Background: Structural congenital heart defects (CHD) take a huge toll of congenital defects in children in India. Limited information is available regarding modifiable risk factors for its causation. This study was planned with an aim to determine the prevalence of congenital rubella infection in Indian infants with structural CHD's. Methodology: This cross-sectional, observational study was conducted at a tertiary care hospital in Northern India over 1 year period (1 July 2016 to 30 June 2017). Infants <6 months with structural CHD were enrolled after taking informed consent from their mothers. Blood samples were collected from mother–child binomials and tested for rubella IgM and IgG antibodies. Results: A total of 80 infants (M : F = 56 : 24), having mean age 69.4 (±56.5) days; were enrolled. In these infants, prevalence of congenital rubella infection (either infant's IgM rubella positive or infant's IgG rubella titers higher than mother's) was 8.75% (7/80). A total of 12.5% of studied mothers were seronegative for rubella IgG antibodies. Statistically significant association was found between the occurrence of congenital rubella and cataract ( p  = 0.0039), splenomegaly ( p  = 0.007) and microcephaly ( p  = 0.0084) in infants having structural CHD. Conclusions: Congenital rubella syndrome still remains an important modifiable cause for structural CHD in India. Sincere efforts for rubella elimination via further strengthening current vaccination strategy would help in decreasing burden of structural CHD in India.